Impact of submacular fluid volume on visual outcome in macula‐off rhegmatogenous retinal detachment using automated optical coherence tomography volumetric quantification. (5th May 2021) - Angermann, Reinhard; Mosböck, Stefan; Palme, Christoph; Ulmer, Hanno; Rauchegger, Teresa; Nowosielski, Yvonne; Bechrakis, Nikolaos E.; Zehetner, Claus
Abstract: Background: We investigated effects of submacular fluid volume (SMFV) on visual outcomes following surgery for macula‐off primary rhegmatogenous retinal detachment (RRD) using automated fluid volumetric quantification with optical coherence tomography (OCT). Methods: We analysed 127 eyes that were surgically treated for macula‐off RRDs. We obtained preoperative images following the spectral domain (SD)‐OCT dense volume protocol, applied automated retinal segmentation and used an automated algorithm to quantify each eye's SMFV. We used multivariate models to identify various risk factors for impaired visual outcome. Results: Linear regression showed that preoperative SMFV (ß = 0.013; P  = .005) was significantly associated with a reduced visual outcome 12 months after the treatment of macula‐off RRDs. SMFV was negatively correlated with 12‐month postoperative ( r  = .311; P  = .001) visual acuity (VA). The group with low preoperative SMFV (≤9.0 mm 3 ) showed an increasing VA up to 12 months postoperatively ( P  < .001), while the VA did not increase in the group with high SMFV (>9.0 mm 3 ) beyond 3 months of follow‐up. Patients with a high SMFV were 8.0 times more likely to have worse visual outcomes after 12 months of follow‐up ( P =  .018). Conclusions: SMFV was negatively correlated with visual outcomes after the surgical treatment of macula‐off RRDs. Patients with SMFV <9.0 mm 3 12 months after surgery had an 8.0 times greater chance for better visual recovery than patients with high preoperative SMFV. Our findings highlight the efficacy of automated SMFV quantification in predicting surgical outcomes in patients with RRDs, which could be useful in future clinical practice and the development of research models.